Broad-Spectrum Cytotoxic Effect of Calendula officinalis L Against Breast Cancer Cells - Khulood M. Alsaraf1, Maeda H. Mohamed1, Ahmed Majeed Al-Shammari2, Ibrahim S. Abbas3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Calendula officinalis L used in Iraqi folklore medicine for several medical applications. This research evaluated the leaves extract as an anti-breast cancer agent in in-vitro cancer cell line systems and studies its active compounds. Crystal violet viability assay was used to determine the cytotoxicity of the leave methanolic extract of Calendula officinalis L against diverse breast cancer cell lines. Human breast cancer MCF7, AMJ13, MDAMB, and CAL51 cells were treated with different concentrations of extract for 72 hours. Morphological study for the exposed cell was done by examination under a phase-contrast inverted microscope. High-performance liquid chromatography (HPLC) analysis was performed to measure the concentrations of each component of phenols and flavonoids in the Calendula officinalis L extract. Results: It was found that methanolic extract of Calendula officinalis L inhibits the proliferation of all breast cancer cells significantly at the meantime; it does not affect normal embryonic cells. Additionally, it induced the cytopathic morphological changes in cancer cells. Furthermore, HPLC study revealed that Calendula officinalis L extract contained an important component of flavonoids. Conclusions: Calendula officinalis L leaves extract inhibited the proliferation of breast cancer cells especially MDAMB cells with no effect on normal cells. This work showed that Calendula officinalis L is a possible natural source as broad-spectrum anti-breast cancer drug.